RELEVANCE OF CHRISTIAN ETHICS IN ADDRESSING CORRUPTION AND SOCIAL JUSTICE ISSUES IN INDONESIA - Thian Rope; Stefanus Sujatmoko; Juan Carlos (International Journal of Education and Literature, 2023)
Basically, if a Christian who serves in government lives outside the control of absolute norms, then he tends to break the rules when carrying out his duties and responsibilities. The Bible teaches that sin is the greatest violation of God's law, so that humans are considered guilty before Him and deserve punishment (Romans 3:23 ; 6:23; Isaiah 59 :2). Acts of corruption are regarded as evil deeds in God's eyes, because they do not meet God's standards in leading (cf. Romans 13 :1-4) and should be God's servants who serve the interests of the people. In principle, followers of the Christian religion are called by God to sit in government with the aim that they can carry out their duties and responsibilities in accordance with the teachings of the Bible. To achieve this, adherents of Christianity are expected to prepare themselves to live in faith and holiness according to the teachings of the Bible. According to the author's opinion, it is very important to build faith from an early age before someone plunges into the world of government. This is so that they can be formed and matured in their faith so that they can become witnesses of Christ in community service. Saint Augustine once said, as Price explained, that if Christians live according to the values of the Bible, then they will show genuine love for others